1997
DOI: 10.1111/j.1469-7998.1997.tb02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of white‐toothed shrews (Crocidura) (Mammalia: Insectivora: Soricidae) of Taiwan: Karyological and morphological Studies

Abstract: With 3 plates and 2 figures in the text)We define the species boundaries of white-toothed shrews (genus Crocidura) in Taiwan using karyological and morphological characteristics. Ninety-nine animals were obtained from all over Taiwan at capture rates usually less than 10%. Three species are recognized by distinct cytotypes:Crociduru uttenuata tanakae 2n = 40, FN = 56; Crocidura suaveolens hoslefti 2n = 40, FN = 50; Crocidura kurodai 2n = 40, FN = 54. A suite of six morphological characters diagnose the three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…attenuata that Heaney & Ruedi (1994) used in their comparisons was originally described as an endemic species ( Crocidura tanakae Kuroda, 1938), later synonymized with C . attenuata (Ellerman & Morrison‐Scott, 1951; Fang et al. , 1997), and then resurrected as a Taiwanese endemic (Fang & Lee, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…attenuata that Heaney & Ruedi (1994) used in their comparisons was originally described as an endemic species ( Crocidura tanakae Kuroda, 1938), later synonymized with C . attenuata (Ellerman & Morrison‐Scott, 1951; Fang et al. , 1997), and then resurrected as a Taiwanese endemic (Fang & Lee, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Heaney & Ruedi (1994) noted the morphological similarity of these specimens from Batan to a series from Taiwan, and tentatively placed the newly discovered population within Crocidura attenuata (Milne-Edwards, 1872), a widespread species then reported from south-central China and Indochina to Taiwan. The Taiwanese population of C. attenuata that Heaney & Ruedi (1994) used in their comparisons was originally described as an endemic species (Crocidura tanakae Kuroda, 1938), later synonymized with C. attenuata (Ellerman & Morrison-Scott, 1951;Fang et al, 1997), and then resurrected as a Taiwanese endemic (Fang & Lee, 2002). Thus, the Taiwanese specimens Heaney & Ruedi (1994) associated with shrews from Batan are now referred to C. tanakae (Smith & Xie, 2008).…”
mentioning
confidence: 99%
“…3). The standard karyotypes of C. kurodai reported by Fang et al (1997) showed the same problem, i.e. the 12th, 13th, 14th, 16th and 17th pairs of chromosome have condensed short arms but the chromatids did not separate.…”
Section: Karyotypementioning
confidence: 82%
“…However, Fang et al (1997) re-evaluated C. h. kurodai as a unique species, C. kurodai, on the basis of differences in karyotype and morphology between samples from central Taiwan and south India. Chromosome numbers and the fundamental number of C. kurodai and C. hors®eldii are reported as 40 and 54 (Fang et al, 1997), and 38 and 48 (Rao & Aswathanarayana, 1978), respectively. Meanwhile, samples of tadae have been too few for reasonable analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Crocidura tanakae Kuroda, 1938 from Taiwan was originally described as a full species but was subsequently considered to be either a synonym or subspecies of Crocidura attenuata (Ellerman and Morrison-Scott 1951, Jameson and Jones 1977, Fang et al 1997, Jiang and Hoffmann 2001, Han et al 2002). Motokawa et al (2001) demonstrated that the karyotype of Taiwanese specimens differed from that of Crocidura attenuata from mainland southern China and suggested that it might represent a distinct species.…”
Section: Background To Identification Of Species Based On Dna Analysismentioning
confidence: 99%